Pengaruh Ukuran Serbuk Simplisia dan Waktu Maserasi terhadap Aktivitas Antioksidan Ekstrak Kulit Sirsak - Riska Yudhistia Asworo; Hanandayu Widwiastuti (Indonesian Journal of Pharmaceutical Education, 2023)
Secondary metabolites are one of the active substances in natural materials that are known to contain high antioxidants and are very beneficial for health. In addition to mangosteen, there are also natural ingredients that actually have high antioxidant content, but many people do not know about it, one of which is soursop fruit. In addition to the fruit, the skin of soursop fruit may contain antioxidants that are quite high. The purpose of this study was to determine the effect of different maceration times and powder sizes on the antioxidant activity of secondary metabolite compounds produced from ethanol-aquades extract of soursop fruit peel (Annona muricata L.). This study was conducted quantitatively with a descriptive research design where researchers conducted laboratory research conducted in triplo. This research used particle size variation of 50 mesh, 100 mesh, and 200 mesh and maceration time variation of 24 hours, 30 hours, 36 hours. From this study it can be seen that the difference in powder size and maceration time affects the results of antioxidant activity obtained. The optimum particle variation is using 200 mesh size, which is obtained antioxidant activity of 95.2%. While the optimum maceration time is for 24 hours, the yield is 94%. From this study it can also be seen that the ethanol-aquades extract of soursop fruit peel contains secondary metabolite compounds of triterpenoids, saponins, polyphenols and tannins.